Glucosamine oral administration as an adjunct to hyaluronic acid injection in treating temporomandibular joint osteoarthritis. (4th October 2017) - Cen, Xiao; Liu, Yan; Wang, Shasha; Yang, Xianrui; Shi, Zongdao; Liang, Xinhua
Abstract : Objective: To investigate the therapeutic effect of oral glucosamine (GS) as an adjunct to hyaluronic acid (HA) injection on patients with temporomandibular joint osteoarthritis (TMJ OA). Methods: In this clinical trial, 136 participants, diagnosed as TMJ OA clinically and radiographically, were enrolled and randomized into two groups (group GS + HA: oral GS + HA injection; group placebo + HA: oral placebo + HA injection). Pain, maximum interincisal mouth opening (MMO), the levels of IL‐1β, IL‐6, and TGF‐β in TMJ synovial were defined as the outcome measurements and conducted before operation, and at 1‐month and 1‐year follow‐up. Results: In both groups, pain scores were decreased and MMOs were increased at 1‐month and 1‐year follow‐up, the changes at 1‐year follow‐up showed statistically significant intergroup differences. At 1‐month follow‐up, only IL‐6 concentration was lower in group GS + HA than that in group placebo + HA. One year later, TGF‐β concentration was higher and IL‐6 and IL‐1β concentrations were lower in group GS + HA than those in group placebo + HA. Conclusions: Both strategies alleviated symptoms in short term, but the patients treated with GS benefited more than those with placebo in long term, which may be due to the suppression of IL‐1β and IL‐6 and the stimulation of TGF‐β.